2020
DOI: 10.3389/fvets.2020.575221
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of the Owner-Bird Relationship Scale (OBRS) to Assess the Relation of Humans to Their Pet Birds

Abstract: Only a few birds besides domestic pigeons and poultry can be described as domesticated. Therefore, keeping a pet bird can be challenging, and the human-avian relationship will have a major influence on the quality of this cohabitation. Studies that focus on characterizing the owner-bird relationship generally use adapted cat/dog scales which may not identify its specific features. Following a sociological approach, a concept of human-animal relationship was developed leading to three types of human-animal rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Two Likert scales were also utilized. The first was the validated OBRS, as per the work of Burmeister et al [34]. This was used in an identical format apart from the references to "bird" being replaced with "chicken", and "it" with "his/her"-alterations that were sanctioned by the original creators of the scale [44].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two Likert scales were also utilized. The first was the validated OBRS, as per the work of Burmeister et al [34]. This was used in an identical format apart from the references to "bird" being replaced with "chicken", and "it" with "his/her"-alterations that were sanctioned by the original creators of the scale [44].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Robertson et al [33] demonstrated how a stronger attachment to pets is positively correlated with positive attitudes towards nonhuman animals. Nevertheless, the concept of relationship involves numerous other parameters too, including interaction (or a lack thereof), support, and empathy/attentiveness, as outlined by Burmeister et al [34]. A plethora of studies have examined the human-animal relationship concerning conventional companion animals, predominantly dogs, cats, and horses.…”
Section: Attitudes Towards Chickens and The Human-chicken Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…This review identified several notable exceptions. One is the well powered study conducted by Burmeister used to develop a scale of people's relationships with their companion birds which recruited n = 1444 participants across Germany [45]. The pair of studies conducted by Ko, Park, and others, included a single-blinded Randomized Control Trial, and a functional Magnetic Resonance Imaging study, on the effect of caring for companion crickets on brain function and overall health [49,53].…”
Section: Companionship Andmentioning
confidence: 99%
“…However, even this body of research is somewhat niche in the scheme of human-animal bonds literature-in a systematic review of humananimal research, birds were only discussed in reference to poultry being kept as agricultural livestock rather than companion animals [6]. Additionally, scientific inquiry into humanbird relationships has tended to use or adapt scales developed for use with dogs and cats, which are likely to miss the nuances inherent in a human-bird relationship owing to fundamental differences in species, daily care and veterinary care, and birds' cognitive and speaking capabilities [45].…”
Section: Companionship and Attachment With Birdsmentioning
confidence: 99%